Welfare impact of asymmetric price transmission on rice consumers in Bangladesh - Rahman, Mohammad Chhiddikur; Pede, Valerien O.; Balié, Jean (Wiley, 2022)
This study investigates asymmetric price transmission (APT) in the rice market in Bangladesh using monthly price series at farm, wholesale, and retail levels from October 2005 to June 2017 in a nonlinear autoregressive distributed lag model (NARDL). The results indicate a significant asymmetric relationship across price at retail, wholesale, and farm levels in the long and short term. While wholesalers/millers benefit from the imperfect price transmission at the expense of farmers, retailers gain over wholesalers/millers. We find that the consumer surplus decreases from a price rise at the wholesale or farm level, but consumers do not enjoy a proportional increase in their surplus from a price reduction. The study reveals that the consumer welfare loss due to APT along the rice value chain of Bangladesh is equivalent to US$89.05 million per month. This estimated aggregate welfare loss requires both the attention of decision‐makers and corrective actions.